Comparative analysis of POD gene family and expression differentiation under NaCl, H2O2 and PEG stresses in sorghum - Linyong Shi; Heng Zhang; Heyun Chen; Heqin Liu; Xiuhui Liu; Xueqiang Zheng; Guihua Zou; Junmei Wang (BMC Genomics)
Abstract Background Sorghum has a strong tolerance to multi-abiotic stresses such as drought, heat, poor soil fertility, and salinity, yet its growth and development are significantly affected by extreme abiotic stresses, ultimately reducing grain yield. Peroxidase (POD) proteins, which are members of the oxidoreductase enzyme family, play an important role in protecting plants against multi-abiotic stress. However, this gene family has rarely been studied in sorghum. Results In this study, 114 POD gene members (SbPODs) were identified in sorghum and distributed unevenly throughout 10 chromosomes. Phylogenetic analysis clustered these genes into 12 subgroups. Gene structure and motif analyses showed the structural and functional diversity among the subgroups. These genes have undergone 16 segmental duplication and 32 tandem duplication events, indicating that both segmental and tandem duplications are major contributors to the expansion of the SbPOD gene family. Most duplicated SbPODs have undergone purifying selection with limited functional divergence during duplication events. Compared with maize, rice, and Arabidopsis, SbPOD gene family not only occurred the duplication on the whole-genome level, but also existed independent duplication events. The qRT-PCR results showed twenty SbPOD genes exhibited differential expression patterns in leaves under NaCl, H2O2 and PEG stress treatments. Of twenty SbPOD genes, most SbPOD genes showed consistently significant downregulation under NaCl, H2O2, and 30% PEG6000 stress treatments, except for SbPOD81 and SbPOD26. Under NaCl stress, the expression level of SbPOD81 showed a down-up regulation trend. Under H2O2 stress, the expression level of SbPOD81 showed a down regulation trend. Under 30% PEG6000 stress, SbPOD81 maintained down-up regulation trend but quite different under NaCl stress. In contrast, the expression level of SbPOD26 showed consistent down-up regulation trend under both NaCl and H2O2 stress, while after 3 h of adaptation under 30% PEG6000 stress, the expression level of SbPOD26 continued to increase. The analysis of cis-elements and conserved domain showed that SbPOD81 contains one W-box, four MYB, and three MYC cis-elements, while SbPOD26 has two W-boxes, four MBS, four MYB, and eight MYC cis-elements. Additionally, SbPOD26 possesses one PAT1 domain, which is absent in SbPOD81 and other SbPOD genes. This structural distinction not only would explain the observed expression divergence but suggests SbPOD26 may perform specialized biological functions distinct from other SbPOD genes. Conclusions Totally, 114 POD gene members were identified in sorghum by a series of bioinformatics analysis. The expression patterns of some members of SbPOD gene family exhibited significantly difference under various stress conditions. These findings not only provide valuable insights into the evolutionary dynamics of the SbPOD gene family, but also lay a foundation for further studies on the functions of POD genes.